2011
DOI: 10.1080/10888705.2011.600186
|View full text |Cite
|
Sign up to set email alerts
|

Managing Feral Cats on a University's Campuses: How Many Are There and Is Sterilization Having an Effect?

Abstract: Worldwide domestic and feral cat (Felis catus) numbers have increased. Concerns regarding high populations of feral cats in urban areas include wildlife predation, public nuisance, and disease. This study aimed to estimate the size of the feral cat population on 5 campuses of the University of KwaZulu-Natal, South Africa, to determine whether sterilization has an effect and to make management recommendations. The study used both the total count and mark-recapture methods to estimate the feral cat population on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Moreover, as of 1st January 2012, Poland's Animal Protection Act has been changed, with the paragraph about shooting free-ranging cats and dogs removed and the problem of stray cats completely disregarded. Instead of lethal control, sterilisation might be attempted, although relatively high sterilization rates are necessary to reduce population sizes (Jones and Downs, 2011), and recent studies have demonstrated that both home ranges size and long distance movements of sterilized and reproductively intact cats did not differ (Levy and Crawford, 2004;Guttilla and Stapp, 2010). Another proposed solution is collars with attached bells or electronic sonic devices, which can reduce cat predation (Nelson et al, 2005;Calver et al, 2007;Gordon et al, 2010) but are not always effective (Paton, 1991;Barratt, 1998;Ruxton et al, 2002;Woods et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, as of 1st January 2012, Poland's Animal Protection Act has been changed, with the paragraph about shooting free-ranging cats and dogs removed and the problem of stray cats completely disregarded. Instead of lethal control, sterilisation might be attempted, although relatively high sterilization rates are necessary to reduce population sizes (Jones and Downs, 2011), and recent studies have demonstrated that both home ranges size and long distance movements of sterilized and reproductively intact cats did not differ (Levy and Crawford, 2004;Guttilla and Stapp, 2010). Another proposed solution is collars with attached bells or electronic sonic devices, which can reduce cat predation (Nelson et al, 2005;Calver et al, 2007;Gordon et al, 2010) but are not always effective (Paton, 1991;Barratt, 1998;Ruxton et al, 2002;Woods et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…The availability of data from 1995 to 2011 on unmanaged cat colonies within the Auckland region provided an opportunity to establish a geographic information system (GIS) for building such an approach. As these colonies were actively resolved, the data provide a valuable insight into the numbers of such cats, especially as individuals often underestimate the colony's size, even if closely associated with it (Jones & Downs, 2011). It will also allow examination of the distribution characteristics of cat colonies and the social and environmental factors that may be relevant.…”
Section: Introductionmentioning
confidence: 99%
“…One model estimates that the per cent sterilization needed to reduce feral cat populations is between 71% and 94%, levels that are rarely reached in real‐world scenarios (Foley et al., ). Similarly, another study concluded that 90% sterilization is necessary to reduce feral cat populations (Jones and Downs, ).…”
Section: Effectiveness Of Tnvr Programmesmentioning
confidence: 99%
“…One model estimates that the per cent sterilization needed to reduce feral cat populations is between 71% and 94%, levels that are rarely reached in real-world scenarios (Foley et al, 2005). Similarly, another study concluded that 90% sterilization is necessary to reduce feral cat populations (Jones and Downs, 2011). Evidence from other model-based analyses of TNR programmes showed that while TNVR may be useful if broadly implemented in closed populations when no animals can immigrate into colonies (e.g.…”
Section: Effectiveness Of Tnvr Programmesmentioning
confidence: 99%